2016
DOI: 10.1074/jbc.m116.749606
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cataract-linked γ-Crystallin Variants in Zebrafish Reveals a Proteostasis Network That Senses Protein Stability

Abstract: Edited by Paul FraserThe refractivity and transparency of the ocular lens is dependent on the stability and solubility of the crystallins in the fiber cells. A number of mutations of lens crystallins have been associated with dominant cataracts in humans and mice. Of particular interest were ␥B-and ␥D-crystallin mutants linked to dominant cataracts in mouse models. Although thermodynamically destabilized and aggregation-prone, these mutants were found to have weak affinity to the resident chaperone ␣-crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 59 publications
5
23
0
Order By: Relevance
“…abnormalities that were readily visible starting at 3dpf ( Figure 1B), without affecting the overall morphology of the embryos ( Figure 1A). The nature of these defects was similar to those previously described for α-crystallin deficient [32,37] or γD-crystallin mutant transgenic lines [33]. Defective lenses exhibited phenotypic features that were either spherical, shiny crystal-like droplets spread sporadically across the lens (minor defects), or frequent droplets covering a large fraction of the lens as well as occasional large irregular protuberances located in the center of the lens (major defects), all of which could lead to opacity and changes in light scattering.…”
Section: Expression Of Both αα-Crystallin Variants Led To Various Degsupporting
confidence: 80%
See 3 more Smart Citations
“…abnormalities that were readily visible starting at 3dpf ( Figure 1B), without affecting the overall morphology of the embryos ( Figure 1A). The nature of these defects was similar to those previously described for α-crystallin deficient [32,37] or γD-crystallin mutant transgenic lines [33]. Defective lenses exhibited phenotypic features that were either spherical, shiny crystal-like droplets spread sporadically across the lens (minor defects), or frequent droplets covering a large fraction of the lens as well as occasional large irregular protuberances located in the center of the lens (major defects), all of which could lead to opacity and changes in light scattering.…”
Section: Expression Of Both αα-Crystallin Variants Led To Various Degsupporting
confidence: 80%
“…In a previous study, we demonstrated that destabilized γD-crystallin mutant proteins formed aggregates in the zebrafish lens with a frequency that strongly correlated with the penetrance of lens defects [33]. Thus, the enhanced lens defects observed in the double transgenic embryos ( Figure 3; αΑ-R49C; γD-I4F) could result from increased aggregation frequency of γD-I4F when the αΑ-R49C transgene was co-expressed.…”
Section: Expression Of αA-r49c Increases the Propensity Of Destabilizmentioning
confidence: 76%
See 2 more Smart Citations
“…The instruments were operated in a data dependent mode with the top five most abundant ions in each MS scan selected for fragmentation in the LTQ. Dynamic exclusion (exclude after 2 spectra, release after 30 sec, and exclusion list size of 150) was enabled 21 .…”
Section: Tandem Mass Spectrometrymentioning
confidence: 99%